The Role of Public Health Workers in Facing the Challenges of Health Development Post-Covid-19 Pandemic: A Review - Nona Carolina; Chalda Bhakti Jelika; Ivani Kartika Cahyani Putri; Anjani Betty Afriani; Trinita Agustia Lasmana (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Covid-19 pandemic is an outbreak of an infectious disease caused by the SARS-CoV-2 virus. This virus can be easily transmitted through direct contact with infected people or by touching objects that have been contaminated. This virus has spread in various countries, one of which is Indonesia. With the spread of this virus, health development in Indonesia is critical. Therefore, to face the challenges of health development after the Covid-19 pandemic, the role of public health workers is very necessary. This study uses a literature review method by collecting data from various journals that discuss the role of public health. This study produced several findings related to the role of public health workers in facing the challenges of health development after the Covid-19 pandemic. These roles include health promotion, environmental health, occupational health and safety, and health care systems.